Implementation Of Hybrid Scheduler In Hadoop - Thirumala Rao, B; Susmitha, M; Swathi, T; Akhil, G (International Journal of Engineering and Technology, 2018)
The paper focusses on priority based round robin scheduling algorithm for scheduling jobs in Hadoop environment. By Using this Proposed Scheduling Algorithm it reduces the starvation of jobs. And the advantage of priority scheduling is that the process with the highest priority will be executed first. Combining the both strategies of round robin and priority scheduling algorithm a optimized algorithm is to be implemented. Which works more efficiently even after considering all the parameters of scheduling algorithm. This proposed algorithm is also compared with existing round robin and priority scheduling algorithms.Â Â